GIL Top Policy Lessons on Increasing Women’s Youth Employment - World Bank (World Bank, Washington, DC, 2020)
Young women in Africa are less likely to be employed than young men, as a result of gaps in access to resources such as skills, time, and capital, and due to underlying social norms. Adolescence is a particularly critical time to intervene, as teenage pregnancy or dropping out of school can have severe impacts on future employment and earnings with significant consequences on their lives. At the macroeconomic level, investing in adolescent girls is also crucial for Sub-Saharan Africa`s demographic dividend.